Factors influencing the germination and emergence of tall windmill grass (Chloris polydactyla) and swollen fingergrass (Chloris barbata) - Albrecht, Alfredo Junior Paiola; Barroso, Arthur Arrobas Martins; Placido, Henrique Fabrício; Silva, André Felipe Moreira; Albrecht, Leandro Paiola; Krenchinski, Fábio Henrique [UNESP]; Filho, Ricardo Victoria; Baccin, Luisa Carolina (My University, 2020)
This study characterized the germination of seeds of Chloris polydactyla (synonymy Chloris elata) and Chloris barbata at varying temperature, luminosity, soil texture and cover. The first experiment WAS conducted in laboratory to determine the temperature and light effects on germination of these species. The experimental design was a 2x7 factorial, where 2 represents the absence/presence of light and 7 temperatures 15, 20, 25, 30, 35, 40 and 45°C. The second experiment was conducted in greenhouse to determine effect of edaphic factors on seedling emergence, in a 3x6 factorial arrangement, consisting of 3 soil textures (sandy, medium and clayey) and 6 sowing depths (0, 1, 2, 4, 6 and 8 cm). The third experiment was conducted in greenhouse to determine soil cover effects and to evaluate the percentage reduction of dry matter of weeds, where the treatments were mulching with 0, 5, 10, 15 and 20 t ha-1 sugarcane straw. All experiments were conducted in completely randomized design, analyzed separately for each species. No seed was germinated under absence of light. Both species achieved better germination in medium textured soil. It was observed that the emergence of the species was low even without straw. Chloris showed better germination under higher temperatures of 30ºC and 35ºC, although exhibited a drastic decline in the emergence with the increase in soil depth or mulching with sugarcane straw. Greater germination of these weeds occurs in medium textured soils.
Keywords: Biology of weeds; luminosity; poaceae weeds; seeds; soil texture; straw; temperature; weeds